TINGKAT PENERIMAAN KONSUMEN TERHADAP TEH DAUN BINAHONG (Anredera cordifolia (Ten.) Steenis) PADA VARIASI SUHU DAN WAKTU PENYEDUHAN - Moh. Syafat Haras; Jan R. Assa; Tineke Langi (COCOS, 2017)
ABSTRACTBinahong leaves tea is an herbal tea that has a distinctive flavor and distinc from the other leaves. The aim of this research is to determine the level of consumer acceptance of binahong leaves tea. The research arranged using Factorial Completely Randomized Design with 2 factors, brewing temperature and brewing time. Analysis of consumer acceptance include taste, color, and aroma of binahong leaves tea. The hedonic test of binahong leaves tea with the highest score of taste, color and aroma is sample on 100 OC of brewing temperature and 7 menit of brewing time.Keywords: herbal tea, binahong leaves, hedonic test